PENGARUH SIKAP TOLERANSI TERHADAP PENERAPAN NILAI-NILAI PANCASILA DI RUKUN WARGA IV KELURAHAN WONOKARTO, WONOGIRI - Nursavitri, Gintha (Educitizen, 2013)
The objective of this research is to investigate the effect of the tolerance attitude on the implementation of the values of Pancasila in Rukun Warga IV of Wonokarto village of Wonogiri regency. The results of this research are as follows: (1) there is a positive and significant effect of the tolerance attitude of the people of Rukun Warga IV of Wonokarto village of Wonogiri subdistrict of Wonogiri regency as indicated by the value of rcount which is greater than that of rtable (0.416 > 0.312); and (2) the contribution of the tolerance attitude as the independent variable to the implementation of the values of Pancasila as the dependent variable is as much as 17.31% whereas the rest 82.69% is affected by the other factors. Based on the results of this research, a conclusion is drawn that there is an effect of the tolerance attitude of the people of Rukun Warga IV of Wonokarto village of Wonogiri regency on the implementation of the values of Pancasila.